Colorectal Liver Metastasis With Intrabiliary Growth: Case Report and Review of the Literature. (May 2014) - Coppola, Sara; Zucchini, Nicola; Romano, Fabrizio; Bovo, Giorgio; Gilardoni, Elisa; Nespoli, Luca; Gianotti, Luca
Colorectal liver metastases with intrabiliary growth are uncommon and difficult to characterize by radiology alone. We present the case of a 61-year-old woman previously operated on for a left colon cancer who developed a metacronous lesion at liver segment II-III. Radiologic workup was indicative for cholangiocarcinoma. Thus, the patient underwent an anatomical left lateral hepatectomy. Pathology showed instead a colorectal metastases with intrabiliary growth. We suggest that in cases of radiological uncertainty between an intrabiliary growth metastasis and a cholangiocarcinoma, the correct surgical strategy should always be an anatomical liver resection without preoperative biopsy because it would not change the operative planning and instead it may increase the risk of dissemination.